The CAHP (cardiac arrest hospital prognosis) score: A tool for risk stratification after out-of-hospital cardiac arrest in elderly patients. (1st March 2020) - Sauneuf, Bertrand; Dupeyrat, Julien; Souloy, Xavier; Leclerc, Maxime; Courteille, Benoit; Canoville, Bertrand; Ramakers, Michel; Goddé, Frédéric; Beygui, Farzin; du Cheyron, Damien; Daubin, Cédric
Abstract: Background: Older age is associated with worse outcome after out-of-hospital cardiac arrest (OHCA). Therefore, we tested the performance of CAHP score, to predict neurological outcome in elderly OHCA patients and to select patients most likely to benefit from coronary angiogram (CAG). Materials and methods: The present study was a retrospective multicentre observational study at 3 non-university hospitals and 1 university hospital. CAHP score was calculated, and its performance to predict outcomes was evaluated. Factors associated with the use of CAG were analysed and the rate of CAG across each CAHP score risk group reported. Results: One hundred seventy-six patients fulfilled inclusion criteria (median age of 81, [79–84]), among which a cardiac cause was presumed for 99 patients. The hospital unfavourable outcome was 91%. The ROC-AUC values for hospital neurological outcome prediction of CAHP score was 0.81 [0.68–0.94], showing good discrimination performance. ST-segment elevation in ECG and initial shockable rhythm were independent factors for performing early CAG, whereas age and distance from the percutaneous coronary intervention centre were independently associated with the absence of early CAG. The percentages of patients receiving early CAG in the low, medium and high CAHP score risk groups were 64%, 33% and 34%, respectively, and differed significantly between low CAHP score risk group and other groups (p = 0.02). Conclusions: The CAHP score exhibited a good discrimination performance to predict neurological outcome in elderly OHCA patients. This score could represent a helpful tool for treatment allocation. A simple prognostication score could permit avoiding unnecessary procedures in patients with minimal chances of survival.